Synergistic Benefits of Combined Aerobic and Cognitive Training on Fluid Intelligence and the Role of IGF-1 in Chronic Stroke. (March 2019) - Ploughman, Michelle; Eskes, Gail A.; Kelly, Liam P.; Kirkland, Megan C.; Devasahayam, Augustine J.; Wallack, Elizabeth M.; Abraha, Beraki; Hasan, S. M. Mahmudul; Downer, Matthew B.; Keeler, Laura; Wilson, Graham; Skene, Elaine; et al.
Background . Paired exercise and cognitive training have the potential to enhance cognition by "priming" the brain and upregulating neurotrophins. Methods . Two-site randomized controlled trial. Fifty-two patients >6 months poststroke with concerns about cognitive impairment trained 50 to 70 minutes, 3× week for 10 weeks with 12-week follow-up. Participants were randomized to 1 of 2 physical interventions: Aerobic (>60% VO2peak using <10% body weight–supported treadmill) or Activity (range of movement and functional tasks). Exercise was paired with 1 of 2 cognitive interventions (computerized dual working memory training [COG] or control computer games [Games]). The primary outcome for the 4 groups (Aerobic + COG, Aerobic + Games, Activity + COG, and Activity + Games) was fluid intelligence measured using Raven's Progressive Matrices Test administered at baseline, posttraining, and 3-month follow-up. Serum neurotrophins collected at one site (N = 30) included brain-derived neurotrophic factor (BDNF) at rest (BDNFresting ) and after a graded exercise test (BDNFresponse ) and insulin-like growth factor–1 at the same timepoints (IGF-1rest, IGF-1response ). Results . At follow-up, fluid intelligence scores significantly improved compared to baseline in the Aerobic + COG and Activity + COG groups; however, only the Aerobic + COG group was significantly different (+47.8%) from control (Activity + Games −8.5%). Greater IGF-1response at baseline predicted 40% of the variance in cognitive improvement. There was no effect of the interventions on BDNFresting or BDNFresponse ; nor was BDNF predictive of the outcome. Conclusions . Aerobic exercise combined with cognitive training improved fluid intelligence by almost 50% in patients >6 months poststroke. Participants with more robust improvements in cognition were able to upregulate higher levels of serum IGF-1 suggesting that this neurotrophin may be involved in behaviorally induced plasticity.